Developing school anti-bullying legislation in Malaysia: with reference to New Jersey and New York state legislation / Athirah Azizan … [et al.] - Azizan, Athirah; Amir, Nuraila Ilia; Harun, Nur Amalina; Hassanor, Siti Norafiqah (Faculty of Law, 2014)
This research paper is carried out to examine the problem of school bullying in Malaysia and the effectiveness of a School Anti-Bullying Legislation in reducing this problem with reference to New Jersey and New York State Legislation. School bullying is a serious matter that affects everyone and occurs everywhere around the world including Malaysia. It can give negative effects to students either physically, psychologically or emotionally depending on the types of bullying whether physical or verbal bullying. Nevertheless, despite the continuance existence of the school bullying problem, Malaysia has no specific legislation to deal with this problem. The existence of the Penal Code (Act 574) and Child Act 2001 (Act 611) are inadequate to curb with the problem of school bullying. Both these legislations contain no specific provision on school bullying. As a result, this problem continues to rise. Besides, the school policies like School Safety policy is still ineffective in reducing bullying activities in school due to lack of enforcement and uniformity between each school. Accordingly, this research paper demonstrates the capability of New Jersey and New York to deal with the problem of school bullying. The availability of a School Anti-Bullying Legislation in these states has shown a decrease in the rate of school bullying. This shows the effectiveness of this legislation to curb with this problem. Due to this fact, this research paper proposes a specific legislation on school bullying to be enacted in Malaysia namely, School Anti-Bullying Legislation.